Gaya Bernyanyi dengan Teknik Bel Canto: (Re)Konstruksi Subjektivitas Penyanyi Perempuan dalam Pertunjukan Musik - Susi Gustina; Timbul Haryono; G.R. Lono L. Simatupang; Triyono Bramantyo (Institut Seni Indonesia Yogyakarta, 2010)
Bel Canto Singing Technique. This article attempting to understand the subjectivity of a woman singer in musicperformance. The poststructuralist feminist perspective is used to focus on the historical and cultural backgroundof the woman’s experiences. Based on the perspective, the research questions refer to: 1) the application of womansinger’s knowledge and cultural perception in songs reproduction so that she can (re)construct her subjectivity; and2) the intention of woman singer to use Western classical music or seriosa in music performance. The life historymethod is used to understand all the subjective experiences of woman singer based on her perspective. The fi ndingsof this research are: 1) subjectivity (re)construction of a woman singer is depend on her knowledge and culturalperception so that her subjectivity is differ from others; and 2) the difference that a woman singer do in musicperformance is related to her intention, i.e. to struggle a music genre that she loves since in the early of her life.